2021
DOI: 10.14569/ijacsa.2021.0120717
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection on Medical Images using Autoencoder and Convolutional Neural Network

Abstract: Detection of anomalies from the medical image dataset improves prognosis by discovering new facts hidden in the data. The present study aims to discuss anomaly detection using autoencoders and convolutional neural networks. The autoencoder identifies the imbalance between normal and abnormal samples. They create learning models flexible and accurate on training data. The problem is addressed in four stages: 1) training: an autoencoder is initialized with the hyperparameters and trained on the lung cancer CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Autoencoder-based approaches have been used in unsupervised anomaly detection for medical images. 31, 32 The generative nature of the ConvVAE makes it possible to perform inference on new data, and any point in the smooth latent space can generate meaningful decodings instead of only minimizing reconstruction loss. In the context of anomaly detection when incoming data can have high variability and project to points on the latent space far from those of the training data, this quality of ConvVAE allows us to use the decoded output for outlier rejection and denoising.…”
Section: Methodsmentioning
confidence: 99%
“…Autoencoder-based approaches have been used in unsupervised anomaly detection for medical images. 31, 32 The generative nature of the ConvVAE makes it possible to perform inference on new data, and any point in the smooth latent space can generate meaningful decodings instead of only minimizing reconstruction loss. In the context of anomaly detection when incoming data can have high variability and project to points on the latent space far from those of the training data, this quality of ConvVAE allows us to use the decoded output for outlier rejection and denoising.…”
Section: Methodsmentioning
confidence: 99%
“…The images are first preprocessed and then trained using autoencoders in which images are designed to receive an input and transform it into a different representation and use various CNN models which are later evaluated with various metrics. The results showed that the proposed approach is worthwhile in detecting anomalies in the CT scan images with an accuracy of 98% and low MSE(Mean Squared Error) [18].…”
Section: Literature Surveymentioning
confidence: 97%
“…Autoencoder-based approaches have been used in unsupervised anomaly detection for medical images. 31,32 The generative nature of the ConvVAE makes it possible to perform inference on new data, and any point in the smooth latent space can generate meaningful decodings instead of only minimizing reconstruction loss. In the context of anomaly detection when incoming data can have high variability and project to points on the latent space far from those of the training data, this quality of ConvVAE allows us to use the decoded output for outlier rejection and denoising.…”
Section: Anomaly Detectionmentioning
confidence: 99%